The causal relationship between trace element status and upper gastrointestinal ulcers: a Mendelian randomization study - Liu, Jianwei; Feng, Gege (Frontiers in Nutrition, 2024)
Background: This study aimed to investigate the bidirectional causal relationships between trace elements (such as zinc, magnesium, phosphate, and folate) and upper gastrointestinal ulcers (including gastric and duodenal ulcers) using a two-sample Mendelian randomization (MR) analysis. Methods: We conducted a two-sample MR analysis using summary-level data from genome-wide association studies (GWAS) obtained from public genomics repositories. We employed various MR methods, including inverse-variance weighted (IVW), MR-Egger, and weighted median methods. Meta-analysis was performed to synthesize results across different datasets. To assess the robustness of our findings, we conducted comprehensive sensitivity analyses, including pleiotropy assessment, heterogeneity tests, and leave-one-out analysis. Results: The findings indicate a positive causal relationship between increased zinc levels and the risk of gastric ulcers, while magnesium and folate appear to offer potential protective effects against gastroduodenal ulcers (P<0.05). Additionally, the meta-analysis supports the causal relationship between zinc and gastric ulcers (P<0.05), confirming zinc's significant causal impact on this condition. Conclusion: The study confirms a positive causal relationship between zinc and gastric ulcers and highlights the complexity of how trace elements are involved in regulating the progression of upper gastrointestinal ulcers. These results provide a scientific basis for dietary recommendations regarding trace element intake in clinical and public health practices and offer new insights into effective prevention and treatment strategies for gastric and duodenal ulcers.